Longitudinal monitoring of power output and heart rate profiles in elite cyclists - Nimmerichter, A.; Eston, R. G.; Bachl, N.; Williams, C. (Journal of Sports Sciences, 2011)
Power output and heart rate were monitored for 11 months in one female (VO2max: 71.5 mL/kg·min) and ten male (VO2max: 66.5 ± 7.1 mL/kg· min) cyclists using SRM power-meters to quantify power output and heart rate distributions in an attempt to assess exercise intensity and to relate training variables to performance. In total, 1802 data sets were divided into workout categories according to training goals, and power output and heart rate intensity zones were calculated. The ratio of mean power output to respiratory compensation point power output was calculated as an intensity factor for each training session and for each interval during the training sessions. Variability of power output was calculated as a coefficient of variation. There was no difference in the distribution of power output and heart rate for the total season (P = 0.15). Significant differences were observed during high-intensity workouts (P < 0.001). Performance improvements across the season were related to low-cadence strength workouts (P < 0.05). The intensity factor for intervals was related to performance (P < 0.01). The variability in power output was inversely associated with performance (P < 0.01). Better performance by cyclists was characterized by lower variability in power output and higher exercise intensities during intervals.